Gambaran Organizational Commitment (Studi Pada Karyawan di Perusahaan BUMN PT XYZ Regional Jabar) - Ifada Auli Azka; Diana Harding; Yus Nugraha (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
The development of technology demands quality human resources. In a company, human resources have an important role that needs to be developed. Organizations need employees who remain to provide the best performance to support the achievement of the goals of the organization. The purpose of this study was to determine the general picture of organizational commitment in PT. West Java Regional XYZ. This type of research is quantitative descriptive, with a total of 128 research subjects. Based on the research results obtained by the commitment of employees of PT. West Java Regional XYZ based on normative commitment is 44%, then continuance commitment is 35% and affective commitment is 21%. These results indicate that the largest component of organizational commitment is normative commitment and the lowest is affective commitment. Suggestions for further researchers to be associated with several factors, such as psychological climate, organizational justice or other factors because it affects how organizational commitment to employees can be formed.